Subscription and Customer Loyalty A Study of Netflix Before and After Covid-19 Pandemic - Kehxheni A/P Paramasivan; Julia Khor Kher Ying; Iffah Nur Syazana Binti Zainal Abidin; Jin Wenji; Akansh KG (Asia Pacific Journal of Management and Education (APJME), 2023)
Since    the    outbreak    of    the    Covid-19pandemic and the implementation of Movement Control Order (MCO) started in Malaysia, consumers couldn’t watch movies in theatres and couldn’t travel anywhere. In order to position itself as a must-have service in the highly competitive streaming industry, Netflix has made considerable investments in original episodes, series, and features. Hence, consumers have subscribed to Netflix, and it has induced a significant increase in its number of subscribers due to the situation. However, as people who have been locked up at home are able to get out and do other things again, Netflix's pandemic-fuelled subscription growth is decreasing significantly faster than expected. Malaysia has entered the endemic phase, with prohibitions on going to the movies being eased and removed. As a result, our team wants to investigate the consumer behaviour of their commitment towards Netflix. We also want to see if the quality of service, pricing, promotion, and convenience affect customers' loyalty to Netflix. We aim to collect 150 Netflix subscribers’ responses and opinions for the research through an online survey. The study will give Netflix a better knowledge of consumer behaviour and recommendations for improving customer retention, especially during the endemic time in Malaysia, when public demand is more elastic toward Netflix's service.